# math

4(x-9)=4(9+1/3x)

Is that 1/(3x) or (1/3)*x?
Cameron G.
17 May 2017
hello peeps I am attaching the solution of this question 4(x-9)=4(9+(x/3))=> x-9=9+x/3=>2x/3=18=>x=27Hope it helps, All the best.
anandchayan
17 May 2017
First off, you divide both sides by 44/4(x-9)=4/4(9+1/3x) => x-9=9+1/3xThen, you add 9 on both sides=> x-9+9=9+9+1/3x=> x=18+1/3xThen, you substract 1/3x from both sides=> x-1/3x=18+1/3x-1/3x=> x-1/3x=18Now, you solve the sum on the left side. If it is (1/3)*x, then => 3/3x-1/3x=18=> 2/3x=18Finally, divide both sides by 2/3=> 2/3/(2/3)x=18/(2/3)=> x=18*3/2=> x=27If it is 1/(3*x), it is a little more complicated;At this point, you substract 18 from both sides:=> x=18+1/3x=> x-18=18-18+1/3x=> x-18=1/3xThen, you multiply both sides times "x"=> (x-18)*x=(1/3x)*x=> x^2-18*x=1/3Then, you substract 1/3 from both sides=> x^2-18*x-1/3=1/3-1/3=> x^2-18*x-1/3=0At this point, you should be able to apply the formula to solve quadratic equations: (-b+-SQRT(b^2-4*a*c))/(2*a), where a=1,b=-18 and c=-1/3=>(-(-18)+-SQRT((-18)^2-4*1*(1/3)))/(2*1)Then you solve both cases (+ and - SQRT), and you should have 2 answers=>(-(-18)+SQRT((-18)^2-4*1*(1/3)))/(2*1)=>(18+SQRT(324-4/3))/2=>(18+SQRT((972-4)/3))/2=>(18+SQRT(968/3))/2Then, your both answers are:(18+SQRT(968/3))/2(18-SQRT(968/3))/2
guillezago
19 May 2017
First you look at the question and observe it once or twice before actually doing something about it. We see that 4 is common on both the sides.So we divide by 4 on both sides and 4 is cancelled. we are left with x-9=9+1/3x. we take 9 on the other sidex=9+9+1/3xnext we have x=18+1/3xtake least common factor of 3x and we getx=(18*3x+1)/3xwe multiply 3x on both sides and we getx*3x=54x+1this gives us the quadratic equation :3x^2 - 54x -1=0applying the quadratic formula (-b+-SQRT(b^2-4*a*c))/(2*a)where a=3, b=-54 and c=-1giving 2 answers those are: 18.01 and -0.018
21 May 2017
Hii friends, I am attaching herewith the answer of this question. X-9 = 9+1/3X3X-27= 27+1X2X=54X=27Hope it will serve your purpose!
lakshika
08 June 2017
Hi dxana,Is this in relation to a graph solution or simple algebra?
Gabby H.
13 June 2017
Given that,4(x-9) = 4(9 + 1/3x)cancelling 4 from both sides, x-9 = 9 + 1/3xx - 1/3x = 9 + 9x(1 - 1/3) = 18x ((3-1)/3) = 18x*2/3 = 18x = (18*3)/2 = 54/2 = 27Therefore, x = 27
priyanka.mangesh
13 September 2017
20171022_201301.jpg
3swayam
22 October 2017
18x+3x
BRITTANY RICHARDS
05 October 2021